Investigation of CO2 avoidance behaviour of membrane capture in post combustion processes - Ek Weis, Daniel (My University, 2011)
Increasing concern for the environment and taxes on carbon dioxide emissions has intensified the development of non-polluting energy supply technologies. Carbon Capture and Storage (CCS) constitute a promising option that can reduce CO2 emissions significantly. State-of-the-art CO2 capture techniques require very high investment costs which will lead to a substantial drop in power plant efficiency. This thesis focuses on energetic and economical investigations of gas separation membrane systems used for post-combustion capture in coal fired power plants. The simulations were carried out with the commercial software packages PRO/II and Aspen Plus. A reference power plant termed the Reference Power Plant North Rhine-Westphalia was chosen for the analyses. On the basis of two membrane cascades, developed by using an ideal flue gas of CO2 and N2, the investigation was carried out using a quasi real flue gas, composed of CO2, N2, O2, H2O and Ar. Although the water content in the flue gas leads to higher energy consumption, a positive effect can be observed: using the same membrane area as in the case with ideal flue gas, the degree of CO2 separation is increased owing to the sweep gas effect of the water content. A detailed heat exchanger investigation was explored for a chosen cascade. The aim was to ensure that the recovered exhaust heat generated from the compression process is sufficient to reheat the retentate in the expansion process. A modification distinguished from the ideal flue gas system was to keep the pressure ratio constant for each pressure section. This makes it possible to have a uniform intercooler design for each stage. A pressure drop of 30 mbar inside each cooler was investigated. This extensive system design results in an energy demand of 292 kWh/tonseparated CO2, a separation degree of 78% and an efficiency loss of 7.9%-points. The system has an energetic advantage in comparison with the MEA absorption method at the same degree of CO2 separation. On the basis of the reference power plant, a comprehensive economic analysis was made, both for CO2 capture cost and CO2 avoidance cost. The results manifest that the heat exchanger cost has a small influence on the total capture cost, which is dominated by the membrane cost in the process. A probable future CO2 emission policy was considered and the CO2 emission cost was included in the calculation. By evaluating the electricity price of the different cases (the reference power plant, the chosen cascade for CO2 capture and the chosen cascade for CO2 avoidance), it was found that high CO2 permeance membranes with long life time and a cheap manufacturing price should be developed to make membrane capture systems more economically competing.
Keywords: Energi; Kemiteknik; Övrig annan teknik; Energy; Chemical Engineering; Other Engineering and Technologies not elsewhere specified